Work-Family conflict, Social support and Job satisfaction: A Cross-Sectional study of Nurses in Pokhara - Adhikari, Divya; Bhattarai, Bal Ram; Gurung, Santosh Kumar; Sharma, Sunita; Bhandari, Pooja (MedS Alliance Journal of Medicine and Medical Sciences, 2023)
INTRODUCTION: Research in the field of nursing has long attempted to address the issue of job dissatisfaction. However, there is scant empirical evidence on work-family conflict and social support in the context of Nepal, both of which are important factors in determining job satisfaction among nurses. Hence, this study examined the role of work-family conflict and social support in determining job satisfaction among nurses in Pokhara. MATERIALS AND METHODS: A descriptive, cross-sectional and correlational study was conducted with a purposive sample of 210 nurses from 10 (public and private) hospitals in Pokhara. Using a Likert-based self-administered structured questionnaire, work-family conflict, social support, and job satisfaction were measured using three separate scales. SPSS 21.0 was used for the correlation and regression analysis of the hypothesized relationships between the variables. RESULTS: The findings revealed that nurses’ job satisfaction was significantly lowered by family-to-work conflicts but not by work-to-family conflicts. The results also demonstrated that social support from management and peers significantly increased nurses’ job satisfaction. CONCLUSIONS: The study concluded that nurses experienced relatively low levels of work-to-family conflict. However, the responsibilities of the home can still affect their job satisfaction. The findings also revealed that social support from both management and coworkers significantly improves nurses' job satisfaction. Implications and suggestions for future study are also presented.